2004
DOI: 10.1023/b:trop.0000012102.42938.90
|View full text |Cite
|
Sign up to set email alerts
|

Preference of Sheep for Three Forms of Mucuna Forage and the Effect of Supplementation with Mucuna Forage on the Performance of Sheep

Abstract: Assessment of the preference of sheep for fresh, dried or ensiled forms of mucuna (Mucuna pruriens var utilis) forage was followed by investigations into the effect of supplementing straw-based diets with the forage. Four sheep were offered fresh, dried and ensiled forms of the forage in a cafeteria style to assess their preference. In the second experiment, 20 sheep were randomly assigned to four dietary treatments, namely, alkali-treated straw only (M0), treated straw supplemented with mucuna forage at 0.3% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
1
0
3
Order By: Relevance
“…The observed lack of effect of dietary MF and MSM incorporation on goat BWG and FCE in the current study corroborates previous studies with goats [58, 77, 78] and cows [79, 80]. Our results, however, disagree with other studies that found improved BWG [81, 82, 83] in sheep and milk yield in cows [84] fed diets supplemented with MF and MSM. They further disagree with those that found decreases in BWG [56, 60, 85], milk yield and liveweight [47] in indigenous goats and growing lambs fed diets supplemented with MSM and whole pods.…”
Section: Discussionsupporting
confidence: 78%
“…The observed lack of effect of dietary MF and MSM incorporation on goat BWG and FCE in the current study corroborates previous studies with goats [58, 77, 78] and cows [79, 80]. Our results, however, disagree with other studies that found improved BWG [81, 82, 83] in sheep and milk yield in cows [84] fed diets supplemented with MF and MSM. They further disagree with those that found decreases in BWG [56, 60, 85], milk yield and liveweight [47] in indigenous goats and growing lambs fed diets supplemented with MSM and whole pods.…”
Section: Discussionsupporting
confidence: 78%
“…The CP content of Mucuna ranges between 132 and 156 g/kg DM according to Mbuthia and Gachuiri (2003). However, higher CP contents (170-210 g/kg DM) have been reported with other varieties of Mucuna harvested at flowering stage (Maasdorp and Titterton, 1997;Adjorlolo et al, 2004). In the current study, Mucuna hay was harvested when the leaves were mature and the long vines were lignified.…”
Section: Discussionmentioning
confidence: 59%
“…Jusqu'à trois (3) mois d'âge, le fourrage frais et les foins ont eu des teneurs relativement élevées en PB. Nos résultats sont légèrement supérieurs à ceux obtenus par Nantoumé et al (2000), Kiema et al (2012), Bahini et al (2016) et Houndjo et al (2018), qui sont compris entre 8,47 et 12,21% MS. Ils sont pour la plupart proches de ceux obtenus par Adjorlolo et al (2001Adjorlolo et al ( et 2004, Muinga et al (2003), Nyambati et Sollenberger (2003), Babatounde et al (2010) et Mahaman et al (2017, qui se situent entre 14,02 et 20,00% MS. Nos teneurs en PB sont par contre relativement faibles comparées à celles indiquées dans la littérature, 23,16 à 26,00% MS par Aboh et al (2002), Houndjo et al (2018) et Nkana et al (2020).…”
Section: Compositions Chimiques Moyennes Des Fourragesunclassified
“…Par contre, les temps de croissance n'ont pas entraîné des hausses sensibles des teneurs en CB et ADF ni des baisses importantes de celles en NDF des foins. Pour la cellulose brute (CB), nos résultats sont légèrement plus élevés que ceux indiqués par Kiema et al (2012) et Mahaman et al (2017, qui sont compris entre 23,12 et 24,49% MS. Nos résultats corroborent globalement ceux de la littérature, 26,30 à 37,50% MS et rapportés par Nantoumé et al (2000), Adjorlolo et al (2001Adjorlolo et al ( et 2004, Aboh et al (2002), Kiema et al (2012), Bahini et al (2016), Mahaman et al (2017 et Nkana et al (2020). Concernant NDF, nos résultats relativement élevés, ne corroborent pas certains de la littérature, 37,40-54,40% MS, obtenus par Adjorlolo et al (2001Adjorlolo et al ( et 2004, Mbuthia et Gachuiri (2003), Muinga et al (2003) et Nyambati et Sollenberger (2003).…”
Section: Compositions Chimiques Moyennes Des Fourragesunclassified
See 1 more Smart Citation